What is known about the types of supports used by culturally and linguistically diverse students and their professional placement educators that facilitate successful learning experiences: A scoping review - Anne Pearson; Anne E Hill; Stacie Attrill; Jodie Copley (Bond University, 2022)
_Purpose:_ Students from culturally and linguistically diverse (CALD) backgrounds can find professional placements challenging. This review aimed to identify evidence regarding how professional placement educators successfully support CALD students during professional placements and to identify research gaps in this area. _Methods:_ Literature searches were conducted in CINAHL, ERIC, SCOPUS, PubMed, PsychNet, Emerald Insight, IEEE and ABI Inform Global databases from 1990 to October 2020 and reference lists of identified papers were also scanned. Data analysis occurred through quantitative (frequency of methodology types) and qualitative analysis methods. This review included a consultation phase with professional placement educators and managers. _Results:_ A total of 109 papers were selected for review. The majority of papers investigated the perceptions of CALD students and placement educators with some papers focussing on support programs undertaken prior to or during placement. _Conclusion:_ It is evident that many gaps exist in the literature regarding the supports placement educators and CALD students use during professional placements. Where programs have been described, they have not measured outcomes robustly. Furthermore, where papers have reported supports, they were often not sufficiently reported to facilitate implementation or replication. Further research is warranted to fully understand how CALD students are successfully supported on placement.